Endometrial microbiome in mares with and without clinical endometritis - Guo, Lulu; Holyoak, G. Reed; DeSilva, Udaya (Frontiers in Veterinary Science, 2025)
Chronic endometritis (CE) is a major contributor to reproductive failure in mares and in many other mammals. Current diagnostic methods lack sensitivity due to the lack of pathognomonic clinical signs or ultrasound findings. Although microbial involvement was suggested, no definitive causative agents have been isolated, and the few studies conducted are compromised by the dependence on culturable aerobic organisms. This study compares the endometrial microbiomes of 13 healthy and 13 CE-diagnosed mares that were carefully matched to their locations and management. Microbial diversity was significantly reduced in CE mares, indicating dysbiosis. Burkholderia and Chlamydia were dominant in both groups but significantly more abundant in CE samples. Linear discriminant analysis revealed Burkholderia, Hyphomicrobium, and Erwiniaceae as significantly enriched in CE. Functional pathway analysis showed increased metabolism-related pathways in CE-associated microbiota, while healthy mares exhibited greater microbial richness and functional diversity. These findings underscore microbial imbalance as a potential driver of CE and highlight the utility of sequencing-based microbiome profiling for improved diagnosis and therapeutic targeting in equine reproductive health. This preliminary study contributes to establishing a uterine microbiome reference for mares, with implications for fertility management.